Asterinid seastars from the Mozambique Channel (Echinodermata: Asteroidea: Asterinidae) - O’loughlin, P. Mark; Mackenzie, Melanie (Zootaxa, 2013)
A new fissiparous asterinid seastar Aquilonastra chantalae sp. nov. is described from Europa Island, one of the Scattered Islands (Les îles Éparses) in the Mozambique Channel. It is compared with the fissiparous asterinid Aquilonastra conan-dae O’Loughlin & Rowe from the Mascarene Islands. A table of distinguishing diagnostic characters is provided. The as-terinid Aquilonastra richmondi O’Loughlin & Rowe is reported forEuropaIsland.